RESPON SISWA TERHADAP KETERAMPILAN MENULIS TEKS PROSEDUR MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Rifa Salsabila; Ika Mustika; Aurelia Sakti Yani (IKIP Siliwangi, 2026)
This research was motivated by the lack of enthusiasm and motivation of students in learning, especially in procedural texts. So to overcome this, an appropriate learning model is needed. The aim of this research is to analyze student responses to procedure learning material using a Problem Based Learning approach supported by the Canva application. This research uses quantitative descriptive methodology. The subjects of this research were class VII students at SMPN 16 Cimahi. One of the data collection techniques used is a Likert scale for graphing student responses. There are some positive statements and some negative statements. The questionnaire data marking technique is carried out by calculating the frequency of responses containing SS (Strongly Agree), S (Agree), TS (Disagree), and STS (Strongly Disagree) for each positive and negative statement. Research findings show that student responses in class are included in the good category, namely 70% positive responses and 30% negative responses.